ANALISIS FAKTOR â FAKTOR YANG BERPENGARUH TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Apriana Dewi, 12.05.52.0025; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
Factors tasted in this study include Profitability, Leverage, Company Size, size of Board of Commissioner and Environmental Performance. This research aims to analyze the factors that influence Corporate Social Responsibility Disclosure on company Manufaktur registered in Indonesia stock exchange.Â The population was all Manufaktur companies in the Indonesia stock exchange in 2012-2014. The sample collection technique used is purposive sampling. The analysis used in this research are multiple linear regression analysis. The results of the testing of hypotheses partial evaluation shows that there are significant positive influence on Company Size and Environmental Performance against Corporate Social Responsibility Disclosure. While for Profitability, Leverage and size of Board of Commissioner there is a positive not significant against Corporate Social Responsibility Disclosure.Keywords: Profitability, Leverage, Company Size, Size Of Board Of Commissioner, Environmental Performance, Corporate Social Responsibility Disclosure